ALALIA IMPROVISATIONAL METHODS OF PREPARATION FOR WORK ON SPEECH IMPAIRMENT (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The article discusses the processes of working on speech impairment in alalia, improvisational methods, speech errors in methods, correction of alalia speech and ways to implement it